A schoolscape in the north of Sweden. Visual representations of the national minority languages Finnish, Meänkieli, and Sami - Brännmark, Theres (Apples - Journal of Applied Language Studies, 2024)
This study investigates how a compulsory school, catering for students from the preschool class to grade nine in the north of Sweden, visually opens spaces in the schoolscape for multilingualism involving the national minority languages, Finnish, Meänkieli, and Sami. The analysed material consists of photographs of language-related images, objects, symbols, and written texts in the school’s common spaces such as entrances, corridors, and stairwells. Geosemiotics is used to analyse discourses and representations of languages in the school environment. Furthermore, the connections between discourses in the schoolscape and the larger context of national policy are explored. The analysis reveals that there is a complete absence of representations of multilingualism in significant parts of the examined schoolscape, and that Finnish, Meänkieli, and Sami are treated as temporary elements with the representations tending to become a museum exhibition, despite the school's ambition to recognise and value the three languages. The study thus demonstrates the complexity of the issue and that the renegotiation of national ideology in a local setting is not unproblematic.